PENINGKATAN TARIF CUKAI ROKOK DAN DAMPAKNYA TERHADAP PEREKONOMIAN DAN PENDAPATAN SEKTORAL JAWA TENGAH - Ashar, Fatoni; ,, Firmansyah (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2015)
This study analyzes the effect of excise of cigarette price changes to the consumption of cigarette andÃ‚Â Central JavaÃ¢â‚¬â„¢s economy and household income. In the first stage, with employing panel data regression model,i.e. fixed effect model (FEM) which include 35 regencies/cities in Central Java Province during 2009-2013, theÃ‚Â study examines the effect of cigarette excise to cigarette consumption. On the next stage, the study simulatesthe impact of cigarette consumption shock to the Central JavaÃ¢â‚¬â„¢s sectoral economy and household income usingÃ‚Â the Central Java 2013 Input-Output table. The findings indicate that the cigarette excise has a tradeoff effect tohouseholdÃ¢â‚¬â„¢s cigarette consumption. The increase of cigarette excise reduces cigarette consumption, and next,Ã‚Â reduces output and sectoral household income. The cigarettes industries suffered the highest impact of thedecrease of the cigarette consumption, followed by other sectors which is has a high link to cigarette industriesÃ‚Â such as agricultures and tobacco sectors.Keywords: cigarette, excise, panel data regression, input-output analysis